Validating the efficacy of GPS tracking vehicle movement for driving behaviour assessment - Sun, Qian (Chayn); Odolinski, R.; Xia, Jianhong (Cecilia); Foster, Jonathan; Falkmer, Torbjorn; Lee, Hoe (2017)
Vehicle movement trajectory recorded by GPS maps the vehicle's lane position in time sequence, therefore theoretically can be used to assess driving behaviour. However, the data quality level which can be achieved for vehicle movement tracking by different GPS receivers and positioning techniques hasn't been fully explored and documented. This study systematically validated the efficacy of GPS recording vehicle movement using different types of receivers and positioning techniques. The receivers include both recreational and professional devices; the positioning techniques refer to Single Point Positioning (SPP), Differential GPS (DGPS) and Real-time kinematic (RTK) solutions. The field trials tested the positioning accuracy as well as the quality of trajectory tracking by comparing the recorded positions to benchmarks. The study findings indicate that vehicle movement trajectories recorded by recreational-grade GPS receivers can only match other spatial information at low resolution, which is limited to the assessment of wayfinding and navigation behaviour. In contrast, the SPP, DGPS and RTK techniques undertaken by professional receivers can raise horizontal accuracy to the metre, decimetre, and centimetre level respectively. For under open sky road driving, the RTK solution generated accurate and precise vehicle movement trajectories sufficient for extracting vehicle lane position, speed, acceleration/deceleration, so as to detect detailed driving events and quantitatively assess individual driver behaviour. This paper serves as a critical reference for other researchers on the different types of GPS receivers and solutions prior to engaging a GPS in their studies.